CONTEMPORARY ISLAMIC JURISPRUDENCE THOUGH IN THE WORK OF KHALED ABOU EL FADL - Qurrotul Ainiyah Aini (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2019)
With a qualitative approach, this research raises Khaled Abou El Fadl's thoughts on contemporary Islamic law discourse by analyzing one of his main works, namely Speaking in God's Name: Islamic Law, Authority, and Women. This paper will be focused on two important questions. First, how is the history of Khaled Abou El Fadl's life? Second, how is Khaled Abou El Fadl’s thought style in the tradition of contemporary jurisprudence? Based on those two questions, this research finally produces that; First, Abou El Fadl grew out of the dialectic of Islamic thought in the Middle East which has grown since the 1970s. His thought was actually a reaction to the rise of Salafi discourses, especially in Saudi Arabia and Egypt. The idea of Abou El Fadl is seen as a moderate wing representation in Salafi thought. Second, Atas Nama Tuhan, Khaled Aboul El Fadl's work is an experiment of his criticism of Salafism ideology which argues that Islamic reformism is also responsible for creating a creed closed, intolerant, and superficial in understanding the sacred texts of Islam should be taken seriously. His thought provides a discourse on Islamic law by combining classical Islamic thought with modern hermeneuticdiscourse.